1985
DOI: 10.1111/j.1365-2125.1985.tb02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific antagonism of adenosine‐induced bronchoconstriction in asthma by oral theophylline.

Abstract: 1 The airway response to increasing concentrations of inhaled adenosine and histamine after oral theophylline or matched placebo was studied in nine asthmatic subjects. Changes in airway calibre were followed as sGaw and FEV1 and concentration-response curves constructed. 2 Inhaled adenosine caused concentration-related bronchoconstriction and was fourfive times less potent than inhaled histamine. 3 Theophylline, which achieved a mean plasma level of 15.9 and 16.6 ,ug/ml on the histamine and adenosine study da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…The mechanism of bronchoconstriction is indirect, and involves release of histamine and leukotrienes from airway mast cells [32,33]. The bronchoconstrictor effect of adenosine is prevented by therapeutic concentrations of theophylline [34]. This confirms the fact that theophylline is capable of antagonizing the effects of adenosine at therapeutic concentrations, but does not necessarily indicate that this is important for its anti-asthma effect.…”
Section: Adenosine Receptor Antagonismsupporting
confidence: 68%
See 1 more Smart Citation
“…The mechanism of bronchoconstriction is indirect, and involves release of histamine and leukotrienes from airway mast cells [32,33]. The bronchoconstrictor effect of adenosine is prevented by therapeutic concentrations of theophylline [34]. This confirms the fact that theophylline is capable of antagonizing the effects of adenosine at therapeutic concentrations, but does not necessarily indicate that this is important for its anti-asthma effect.…”
Section: Adenosine Receptor Antagonismsupporting
confidence: 68%
“…However, the bronchodilator effect of theophylline in chronic asthma is small in comparison with β-agonists. Several studies have demonstrated a small protective effect of theophylline on histamine, methacholine, distilled water or exercise challenge [34,[53][54][55][56][57]. This protective effect does not correlate well with any bronchodilator effect, and it is interesting that in some studies the protective effect of theophylline is observed at plasma concentrations of < 10 mg·l -1 [54,55].…”
Section: Airway Smooth Muscle Effectsmentioning
confidence: 99%
“…Theophylline, a nonselective adenosine receptor antagonist, selectively (relative to histamine) inhibited adenosine-induced bronchoconstriction at doses generating plasma concentrations that are insufficient to inhibit phosphodiesterases but well above those needed to block adenosine receptors (22). Moreover, both rebound hyperresponsiveness to adenosine and exacerbation of symptoms have been reported when chronic theophylline therapy was withdrawn (36).…”
mentioning
confidence: 99%
“…Administration by inhalation of adenosine, or its precursor AMP, induces bronchospasm in patients with asthma and COPD, but not in normal controls (3,4). Adenosine-induced bronchoconstriction is most likely mediated by activation of mast cells because this effect is blocked not only by adenosine receptor antagonists (5), but also by selective H 1 blockers (6, 7) and chromolyn sodium (8). Inhaled adenosine has been shown to increase levels of mast cell mediators such as histamine and tryptase in bronchoalveolar lavage fluid from asthmatics (9).…”
mentioning
confidence: 99%